THE PROBLEM OF ENSURING UNINTERRUPTED EXPLOITATION OF WELLS ON THE FIELDS AT THE LATE STAGE OF OPERATION - Yulianna O. Sizova; Sergey A. Parosochenko; Alexey N. Grab (Вестник Северо-Кавказского федерального университета, 2022)
The design of a ramjet wellhead choke, with automatic cleaning throttle channel, which can set in the axial channel of pipe at the wellhead. When the differential pressure increase, which occurs in the case of the axial channel nozzle clogging with mechanical impurities or gas hydrates, automatically the needle will have inserted in the axial throttle channel with mechanical impact to the layer deposition. In this time the product of the well's goes through the annular channel (bypass), the differential pressure will recovered. After that the details of the device take a starting position, with the continuation of the process of working as before, through the throttle channel.